Taxonomy and bioacoustics of some crickets (Orthoptera: Grylloidea) from Panti Forest Reserve (Peninsular Malaysia: Johor) - Tan, Ming Kai; Muhammad, Amira Aqilah; Gorochov, Andrei V.; Abdullah, Nurul Ashikin (Zootaxa, 2024)
Orthopteran surveys were recently conducted at the Panti Forest Reserve in Johor State of Peninsular Malaysia. Based on new material, three species new to science are described here: Agryllus sori Tan, Muhammad & Gorochov, sp. nov. (Gryllidae: Gryllinae), Malayzacla panti Tan, Muhammad & Gorochov, gen. et sp. nov. (Phalangopsidae: Phalangopsinae) and Parendacustes (Parendacustes) aduncus Tan, Muhammad & Gorochov, sp. nov. (Phalangopsidae: Phalangopsinae). The calling songs of five species are described here for the first time: Agryllus sori Tan, Muhammad & Gorochov, sp. nov., Duolandrevus (Bejorama) firmus tiomani Gorochov, 2016 (Gryllidae: Landrevinae), Malayzacla panti Tan, Muhammad & Gorochov, gen. et sp. nov., Parendacustes (Parendacustes) aduncus Tan, Muhammad & Gorochov, sp. nov. and Trellius (Protrellius) helverseni tioman Gorochov, 2011 (Phalangopsidae: Phaloriinae). New locality records in Panti Forest Reserve for five species are also presented here: Duolandrevus (Bejorama) firmus tiomani Gorochov, 2016, Duolandrevus (Bejorama) parvulus Gorochov, 2016, Brevimunda trilineata Tan, Japir, Chung & Robillard, 2022 (Oecanthidae: Podoscirtinae), Zamunda fuscirostris (Chopard, 1969) (Oecanthidae: Podoscirtinae) and Trellius (Protrellius) helverseni tioman Gorochov, 2011.